2017
DOI: 10.1186/s12014-017-9158-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a blood-based classifier for diagnostic evaluation of asymptomatic individuals with pulmonary nodules

Abstract: BackgroundThe number of pulmonary nodules detected in the US is expected to increase substantially following recent recommendations for nationwide CT-based lung cancer screening. Given the low specificity of CT screening, non-invasive adjuvant methods are needed to differentiate cancerous lesions from benign nodules to help avoid unnecessary invasive procedures in the asymptomatic population. We have constructed a serum-based multi-biomarker panel and assessed its clinical accuracy in a retrospective analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Although LDCT screening for lung cancer is associated with the low specificity (73.4%)4 and the resulting high rate of false-positives (96.4%),3 annual LDCT-screening for lung cancer was recently recommended for high-risk individuals 5. However, in this recommendation, the need for more research into the use of biomarkers to complement LDCT screening was also stressed 56…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although LDCT screening for lung cancer is associated with the low specificity (73.4%)4 and the resulting high rate of false-positives (96.4%),3 annual LDCT-screening for lung cancer was recently recommended for high-risk individuals 5. However, in this recommendation, the need for more research into the use of biomarkers to complement LDCT screening was also stressed 56…”
mentioning
confidence: 99%
“…The main concern raised by clinicians performing lung cancer CT screening is the high prevalence of one or more lung nodules, with many being undiagnosed as either malignant or benign 36. In Korea, LDCT screening showed that 35% of subjects had at least one or more non-calcified lung nodule, and lung cancer detection rates were 0.36% 14.…”
mentioning
confidence: 99%